Administration and Results of a State Alternate Assessment Based on Alternate Academic Standards in Science for Students Who Are Blind and Have Low Vision. (January 2023) - McCarthy, Tessa; Schles, Rachel Anne; Moore, Debra W.
Introduction: This study evaluated performance and engagement on the tactile science alternate assessment based on alternate academic standards (AA-AAS). This assessment was designed for students with significant intellectual disabilities and visual impairments (i.e., blindness and low vision). Four primary research questions guided this study. What were the demographic characteristics of the students who took the tactile AA-AAS-science? How did students who took the tactile AA-AAS-science perform? What accommodations, accessibility options, and communication strategies were employed in the administration of the tactile AA-AAS-science? Was there a correlation between any administration practices and improved student results?Methods: Thirty-four students with visual impairments and significant intellectual disabilities participated in the 2017 administration of the AA-AAS-science. Post-hoc analyses of the testing strategies were conducted using video recordings of each assessment. Videos were coded for accommodations, student performance, engagement, and appropriateness of the assessment for each student.Results: The tactile materials were the primary accommodation provided to students and were totally novel in 79.1% of the administrations. Students were not permitted to thoroughly explore materials. In many cases, the exam content was determined to be too difficult for the students.Discussion: This study supports the literature and suggests benefits in academic instruction for all students. For academic instruction to be meaningful, students need appropriate accommodations and consistent materials.Implications for Practitioners: Test administrators for assessments based on alternate academic standards should use familiar materials during a test administration, preferably the same materials used during instruction. It is also important for teachers to prepare students and allow for time to systematically explore tactile materials. Teachers can support students by including academic goals in the individualized education program.